2020
DOI: 10.3389/fpsyg.2020.01213
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors in the Typical Display of Humor and Creative Potential: The Case of Malevolent Creativity

Abstract: Research is still disputing if an individual's use of humor in everyday life is also indicative of his or her creative potential. To date, the focus has been mainly restricted to shared cognitive factors, while motivational aspects that may link the production of humor and of creative ideas have been largely neglected. Humor motivation implicates latent social goals the creator pursues through the use of humor. These goals can be benign or more malicious and manifest in an individual's typical display of comic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Antagonism (but not negative affectivity, detachment, disinhibition, or psychoticism as measured by the Personality Inventory for DSM-5) also emerged as a unique predictor of malevolent creativity in the MCT (Perchtold-Stefan et al, 2020b). A higher capacity for malevolent creative ideation was further reported for individuals with a higher preference for using dark, malicious humor (e.g., sarcasm, irony, cynicism; Perchtold-Stefan et al, 2020a). For an interpretation, the authors suggested shared motivations in the generation of malicious ideas and the use of dark humor, which may be attributed to latent interpersonal goals aimed at hurting, upsetting, or dominating others (Papousek, Ruch, et al, 2017).…”
Section: Linking Malevolent Creativity To Personality Traits Social G...mentioning
confidence: 92%
“…Antagonism (but not negative affectivity, detachment, disinhibition, or psychoticism as measured by the Personality Inventory for DSM-5) also emerged as a unique predictor of malevolent creativity in the MCT (Perchtold-Stefan et al, 2020b). A higher capacity for malevolent creative ideation was further reported for individuals with a higher preference for using dark, malicious humor (e.g., sarcasm, irony, cynicism; Perchtold-Stefan et al, 2020a). For an interpretation, the authors suggested shared motivations in the generation of malicious ideas and the use of dark humor, which may be attributed to latent interpersonal goals aimed at hurting, upsetting, or dominating others (Papousek, Ruch, et al, 2017).…”
Section: Linking Malevolent Creativity To Personality Traits Social G...mentioning
confidence: 92%
“…The ability to create humor-to come up with ideas and practices that make others laugh-is a growing topic in the psychology of creativity. Humor creation dovetails naturally with popular theories and themes in creativity research (Lu et al, 2019;Perchtold-Stefan et al, 2020;Ruch & Heinz, 2019), which has long been concerned with how people generate ideas that are both new and apt for a particular purpose, audience, or context (Diedrich et al, 2015;Sawyer, 2006). In this view, humor production falls under the broader umbrella of creative cognition.…”
Section: Creativity and Humor Productionmentioning
confidence: 99%
“…Initial papers on the dark side of creativity outlined this behavior in artistic, technological, scientific, and organizational domains (McLaren, 1993). Subsequent work has expanded to terrorist and criminal activity (Cropley et al, 2008), video games (Cropley, 2015), educational settings (Kapoor, 2019), dark humor (Kapoor & Karandikar, 2019;Perchtold-Stefan et al, 2020b), and social media (de Saint Laurent et al, 2020). It is easy to consider other potential additions, such as advertising, propaganda, and interpersonal communication (such as the spread of fake news or misinformation).…”
Section: Domainmentioning
confidence: 99%